Pengembangan e-Modul Hidrokarbon Berbasis Inquiry Based Learning untuk Meningkatkan Pemahaman Siswa SMA - Faisal, Razka Aptana Anargya; Lisdiana, Hayyun; Astuti, Tiwi Nur (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2024)
Chemistry learning at the high school level is often considered difficult due to the abstract nature of the material and the lack of interactive teaching materials that support students' learning styles. This study aims to develop and test the effectiveness of an Inquiry-Based Learning (IBL) e-Module on Hydrocarbons as an interactive teaching resource. The research method used is Research and Development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Data collection was conducted through student needs questionnaires and interviews with teachers at SMAN 3 Kota Tangerang, followed by validation by experts and a trial with students from class XI7. The results show that the developed e-Module has excellent quality based on expert validation and received positive feedback from students during the trial. Students found the module engaging, easy to understand, and effective in helping them grasp the concepts of hydrocarbons through the IBL steps. Therefore, this e-Module can serve as an innovative alternative in chemistry learning, particularly for the hydrocarbons topic, to create a more interactive and enjoyable learning experience.